Experimentation of a smart-planning approach for the sustainable renewal of the building heritage of smaller Sardinian historic centers. - Pili, Stefano (Springer, 2018)
The contribution discusses the results of an experiment on smart-planning approach configured as a territorial observatory. The definition of a methodological approach for an observatory for sustainable regeneration of the building heritage of Sardinian Historical Centers (HC) is the main target of the research work. The observatory aims to support the Local Administrations (LA), mainly of the small communities characterized by a lack of resources, in designing, assessing and monitoring policies and actions, providing a tool to build shared knowledge for stakeholders. The general framework of the observatory is consistent with the drawing process of the Detailed Plans of the Historic Centers "DPHC" (Piani Particolareggiati del Centro Storico "PPCS"). It is configured as a multi-customer Web-GIS portal that encompasses a set of multidisciplinary indicators based on Open GeoData and baseline DPHC knowledge, combined with the Voluntary Geographic Information (VGI) derived from the feedback of the portal users. Thanks to recent funding for the DPHC, some extraordinarily detailed studies on the historical building heritage are now available, characterized by a certain uniformity that can be an excellent baseline data to identify a shared set of indicators. The definition of a dynamic, multidisciplinary and multi-scalar set of indicators is one of the key issues of the research work. Such set should be consistent with the local development strategies and with the specific regulatory context. The set of indicators outlines a "BASE Scenario" that could be adopted for the monitoring of the effectiveness of the plan and for the creation and assessment of several scenarios. The spatial structure of the indicators is formulated to embrace several levels of detail: aggregated indicators could be used for HC benchmarking and more detailed indicators could be a useful resource for designing scenarios and monitoring the plan. After a short presentation of the observatory framework, the paper focuses on the indicators and methodologies adopted for the energy efficiency and use of the building heritage. The energy-efficiency indicators are mainly calculated by a GIS procedure that is capable of performing Standard calculations (UNI 11300: 2014) for each building using the DPHC baseline data. The indicators about the use of the building are a synthesis of the results of a questionnaire survey addressed to the inhabitants of the historic centers. Finally, the paper reports the results of an experiment carried out on a Sardinian center. The experiment identifies some critical points and potentialities about the adopted energy-efficiency indicators and about the observatory's general framework that will be the base for further developments.
Keywords: Historische Stadt; Kulturerbe; Historisches Gebäude; Stadterneuerung; Energieeffizienz; Kommunale Zusammenarbeit; Raumbeobachtung; GIS